Endoscopic internal drainage and low negative-pressure endoscopic vacuum therapy for anastomotic leaks after oncologic upper gastrointestinal surgery - Jung, Carlo Felix Maria; Hallit, Rachel; Müller-Dornieden, Annegret; Calmels, Mélanie; Goere, Diane; Chaput, Ulriikka; Camus, Marine; Gonzalez, Jean Michel; Barthet, Marc; Jacques, Jérémie; Legros, Romain; Barrioz, Thierry; Kück, Fabian; Seif Amir Hosseini, Ali; Ghadimi, Michael; Kunsch, Steffen; Ellenrieder, Volker; Wedi, Edris; Barret, Maximilien (Endoscopy, 2021)
Background Endoscopic internal drainage (EID) with double-pigtail stents or low negative-pressure endoscopic vacuum therapy (EVT) are treatment options for leakage after upper gastrointestinal oncologic surgery. We aimed to compare the effectiveness of these techniques. Methods Between 2016 and 2019, patients treated with EID in five centers in France and with EVT in Göttingen, Germany were included and retrospectively analyzed using univariate analysis. Pigtail stents were changed every 4 weeks; EVT was repeated every 3–4 days until leak closure. Results 35 EID and 27 EVT patients were included, with a median (interquartile range [IQR]) leak size of 0.75 cm (0.5–1.5). Overall treatment success was 100 % (95 % confidence interval [CI] 90 %–100 %) for EID vs. 85.2 % (95 %CI 66.3 %–95.8 %) for EVT (P = 0.03). The median (IQR) number of endoscopic procedures was 2 (2–3) vs. 3 (2–6.5; P = 0.003) and the median (IQR) treatment duration was 42 days (28–60) vs. 17 days (7.5–28; P < 0.001), for EID vs. EVT, respectively. Conclusion EID and EVT provide high closure rates for upper gastrointestinal anastomotic leaks. EVT provides a shorter treatment duration, at the cost of a higher number of procedures.